2021
DOI: 10.5604/01.3001.0015.5714
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Self-Sufficiency Level of Selected Countries in Central and Eastern Europe in Poultry Meat Production

Abstract: One of the key markets of the European Union is the poultry meat market. The situation on this market is of significant importance to both producers and consumers. The main aim of the article is to study the level of self-sufficiency of selected countries in Central and Eastern Europe in the production of poultry meat. Eleven countries were selected as the research area: Bulgaria, Croatia, the Czech Republic, Estonia, Lithuania, Latvia, Poland, Romania, Slovakia, Slovenia and Hungary. In the conducted research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…The number of poultry farms in Poland has been gradually increasing in recent decades. Although Poland is the largest producer of poultry meat from the region of Central and Eastern Europe [17], there are not enough data about R. anatipestifer strains isolated from poultry in the country. Given the potential threat of the spread of Riemerella bacteria among poultry and the increasingly observed phenomenon of bacterial resistance to antibiotics, it is particularly necessary to know the sensitivity of strains found in this area.…”
Section: Introductionmentioning
confidence: 99%
“…The number of poultry farms in Poland has been gradually increasing in recent decades. Although Poland is the largest producer of poultry meat from the region of Central and Eastern Europe [17], there are not enough data about R. anatipestifer strains isolated from poultry in the country. Given the potential threat of the spread of Riemerella bacteria among poultry and the increasingly observed phenomenon of bacterial resistance to antibiotics, it is particularly necessary to know the sensitivity of strains found in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Research issues are of great interest, both in domestic and foreign literature. The problem of food self-sufficiency was investigated by Polish researchers, including: Agnieszka Baer-Nawrocka [2002,2014], Iwona Szczepaniak [2012], Franciszek Kapusta [2012], Aneta Mikuła [2012], Pavel Kotyza and Josef Slaboch [2014], Krzysztof Firlej and Sebastian Kubala [2021], Sebastian Kubala and Marcin Stanuch [2021]. A rich resource of research can also be found in the case of foreign researchers : Anita Tiraspolsky [1980], Zdenka Gebeltova [2012], Steffen Noleppa and Matti Cartsburg [2013], Jean-Christophe Bureau and Johan Swinnen [2018], Stephen Wegren andChristel Elvestad [2018], Tatjana Brankov et al [2021].…”
Section: Introductionmentioning
confidence: 99%